Bioethanol Production From Coconut Coir Using Ozonolysis-Hydrolysis-Fermentation-Distillation-Silica Gel Adsorption Method - Maharani, Dinah Wika (Sriwijaya Journal of Environment, 2024)
The utilization of coconut coir as a feedstock for bioethanol production offers an innovative approach to valorize agricultural residues in the South Sumatra region. Given the high lignin content of coconut coir, a lignin removal pretreatment was necessary to enhance the accessibility of cellulose for hydrolysis. This study investigated the impact of ozonolysis duration on lignin and cellulose content, efficacy of silica gel adsorption. The experimental design involved ozonolysis, hydrolysis, fermentation, distillation, and silica gel adsorption. Results revealed that 25 minutes of delignification significantly reduced lignin content by 8,3% while increasing cellulose content by 3,1%. Optimal ozonolysis conditions, coupled with pH stabilization at 4.5 using NaOH, led to enhanced 500 mL bioethanol volume after 7 days fermentation. Application of 10 grams white silica gel for 60 minutes showed an ethanol content of 97% from GC-MS analysis.